DECONSTRUCTION OF ANIES BASWEDAN’S POLITICAL IMAGE ON TWITTER THROUGH THE HASHTAG #ANIESGABENERPEMBOHONG - Arlan Siddha; Widuri Wulandari (Universitas Padjadjaran, 2023)
This paper aims to find out the deconstruction of a political image in the social media space with an interesting contemporary phenomenon to observe through #AniesGabenerPembong which was trending on Twitter in October, at the same time as the announcement of Anies Baswedan’s candidacy as a presidential candidate in 2024 by the NasDem Party. Social media as a means of two-way communication is used as a communication platform to shape the political image of elites or political parties. Twitter is one of the media that is used as a means to spread political messages quickly to form public opinion. This study uses a qualitative method with data analysis using the NVivo software on the NCapture feature to find the connection between #AniesGabenerPembohong and interactions created through Twitter social media accounts. This study shows that social media is used as a means for political elites and other users to spread political messages, in this case, to deconstruct the political image of Anies Baswedan and the NasDem Party and posts related to hashtags revolve around the topic of Anies’ failure as governor of DKI. Jakarta and efforts to degrade the NasDem party as the party that carries Anies Baswedan in the presidential election in 2024.